Boosting performance of lanthanide magnetism perovskite for advanced oxidation through lattice doping with catalytically inert element - Miao, J.; Duan, Xiaoguang; Li, J.; Dai, J.; Liu, B.; Wang, Shaobin; Zhou, W.; Shao, Zongping (Elsevier BV, 2019)
© 2018 ABO3-type perovskite oxides, characterized by high structural flexibility, have found potential applications in many redox processes, including as catalysts for advanced oxidation in wastewater remediation. Here, we demonstrated that by doping the generally believed catalytically inert A-site of LaMnO3(LMO) perovskite with strontium, the catalytic performance for advanced oxidation is surprisingly boosted. Specifically, La0.4Sr0.6MnO3-d(LSMO46) was designed which exhibited a high specific activity (0.0608 min-1m-2) for peroxymonosulfate (PMS) activation, ~6 times that of LMO and ~41 times that of reported nanosized MnFe2O4and Fe/Fe3C. The superior activity was also embodied by low activation energy (44.3 kJ mol-1). Moreover, LSMO46 displayed a lower metal leaching and a better reusability than LMO and Fe/Fe3C and easy catalyst recovery for its magnetic behavior. Such enhanced catalytic activity was attributed to the positively-charged surface (8.3 mV) that favored the adsorption of negatively-charged organics and the presence of a large amount of surface anion defects (oxygen vacancies), created by the doping, that induced the generation of considerable amount of singlet oxygen (1O2) which was demonstrated as the dominant reactive species by selective radical scavenging and EPR trapping. A coupled activation mechanism involving major singlet oxygen and minor free radicals was further proposed for the effective decomposition of organics in LSMO46/PMS system. The findings in this study thus provide us a new strategy for the development of efficient catalysts for advanced oxidation in environmental treatment.